Stop this waste of people, animals and money - Moher, David; Shamseer, Larissa; Cobey, Kelly D.; Lalu, Manoj M.; Galipeau, James; Avey, Marc T.; Ahmadzai, Nadera; Alabousi, Mostafa; Barbeau, Pauline; Beck, Andrew; Daniel, Raymond; Frank, Robert; et al. (Nature (London), 2017)
Predatory journals are easy to please. They seem to accept papers with little regard for quality, at a fraction of the cost charged by mainstream open-access journals. These supposedly scholarly publishing entities are murky operations, making money by collecting fees while failing to deliver on their claims of being open access and failing to provide services such as peer review and archiving.